The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d2qm01380k
|View full text |Cite
|
Sign up to set email alerts
|

Degradable flexible piezoelectric nanogenerator based on two-dimensional barium titanate nanosheets and polylactic acid

Abstract: With the increasing demand for green energy, piezoelectric nanogenerators (PNGs) have attracted extensive attention in energy harvesting. In this work, a high-performance PNG was successfully fabricated from BaTiO3 (BT) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It is worth noting that the organic components of the nanocomposite film could completely be degraded in 0.3 mol/L NaOH over 30 h, enabling the harmless processing of the waste PENG device. 29 PVDF-HFP/TiO 2 9.7 no 9 15 PLA/KNN@PDA 13 1.4 yes 10 20 BC/V-ZnO 1.5 0.08 0.06 yes 11 44…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the organic components of the nanocomposite film could completely be degraded in 0.3 mol/L NaOH over 30 h, enabling the harmless processing of the waste PENG device. 29 PVDF-HFP/TiO 2 9.7 no 9 15 PLA/KNN@PDA 13 1.4 yes 10 20 BC/V-ZnO 1.5 0.08 0.06 yes 11 44…”
Section: Discussionmentioning
confidence: 99%
“…However, above 10 phr, the V p-p tended to deviate from proportionality under the same pressure. This deviation may be attributed to the increased concentration of BTNPs, leading to agglomeration in the nanoweb and subsequently enhancing the stiffness of the composite web [11]. This, in turn, results in reduced piezoelectric deformation under the same pressure.…”
Section: Sensor Performancesmentioning
confidence: 99%
“…Recent studies have demonstrated that the incorporation of nanorods or particles, such as ZnO [7], InN [8], and GaN [9], into PVDF or PVDF/TrFE can improve their piezoelectric characteristics. There has been a considerable rise in the number of studies focusing on piezoelectric PLA materials, and integrating nanorods or particles has also garnered significant interest [10][11][12]. BaTiO 3 nanoparticles (BTNPs) are ferroelectric material with a Polymers 2024, 16, 347 2 of 9 high piezoelectric strain constant (d 33 = 300-400 pC/N), and enhanced remnant polarization is exhibited after electrospinning a binary composite of PLA and BTNPs.…”
Section: Introductionmentioning
confidence: 99%
“…A more eco-friendly approach to E-skin manufacturing appears to be desirable (Xu et al, 2023). The idea of reusing or degrading E-skin is becoming a reality (Zhao et al, 2023). Some E-skins that exhibit superior biocompatibility and non-polluting properties such as hydrogel E-skin have become candidates for the next-generation of biodegradable E-skin.…”
Section: Prospectsmentioning
confidence: 99%